Features of coatings deposition in combined stationary-pulsed operation mode of the magnetron sputtering system - Chunadra, А.G.; Sereda, К.N.; Tarasov, I.K.; Bizukov, А.А.; Girka, A.I. (Вопросы атомной науки и техники, 2017)
The results of researches of the combined stationary-pulsed operating mode of longitudinal planar magnetron sputtering system (MSS) with a magnetically isolated anode and with the additional pulsed high-current, high-voltage power supply are presented. It is shown that the increasing of duration of the pulse discharge with decaying current and voltage is not advisable for effective intensification of MSS target sputtering process and increase of mass transfer of substance on substrate. The existence of the optimal ratio between parameters of the stationary and pulsed magnetron discharge is shown. Представлены результаты исследований комбинированного стационарно-импульсного режима работы продольной планарной магнетронной распылительной системы (МРС) с магнитоизолированным анодом с дополнительным импульсным сильноточным высоковольтным источником питания. Показано, что для эффективной интенсификации процесса распыления мишени МРС и увеличения массопереноса вещества на подложку нецелесообразно увеличивать длительность импульсного разряда со спадающими импульсными током и напряжением. Показано существование определённого оптимального соотношения между параметрами стационарного и импульсного магнетронных разрядов. Представлено результати досліджень комбінованого стаціонарно-імпульсного режиму роботи повздовжньої планарної магнетронної розпилювальної системи (МРС) з магнітоізольованим анодом з допоміжним імпульсним сильнострумовим високовольтним джерелом живлення. Показано, що для ефективної інтенсифікації процесу розпилення мішені МРС та збільшення масопереносу речовини на підкладку небажано збільшувати тривалість імпульсного розряду зі спадаючими імпульсним струмом та напругою. Показано існування визначеного оптимального співвідношення між параметрами стаціонарного та імпульсного магнетронних розрядів.